The AAA+ proteins Pontin and Reptin enter adult age: from understanding their basic biology to the identification of selective inhibitors - Matias, Pedro M.; Baek, Sung Hee; Bandeiras, Tiago M.; Dutta, Anindya; Houry, Walid A.; Llorca, Oscar; Rosenbaum, Jean (Frontiers in Molecular Biosciences, 2015)
Pontin and Reptin are related partner proteins belonging to the AAA+ (ATPases Associated with various cellular Activities) family. They are implicated in multiple and seemingly unrelated processes encompassing the regulation of gene transcription, the remodeling of chromatin, DNA damage sensing and repair, and the assembly of protein and ribonucleoprotein complexes, among others. The 2nd International Workshop on Pontin and Reptin took place at the Instituto de Tecnologia Química e Biológica António Xavier in Oeiras, Portugal on October 10-12, 2014, and reported significant new advances on the mechanisms of action of these two AAA+ ATPases. The major points under discussion were related to the mechanisms through which these proteins regulate gene transcription, their roles as co-chaperones, and their involvement in pathophysiology, especially in cancer and ciliary biology and disease. Finally, they may become anticancer drug targets since small chemical inhibitors were shown to produce anti-tumor effects in animal models.